Hypoxia alters the response of ovarian cancer cells to the mitomycin C drug - Gawrylak, Aleksandra; Brodaczewska, Klaudia; Iwanicka-Nowicka, Roksana; Koblowska, Marta; Synowiec, Agnieszka; Bodnar, Lubomir; Szczylik, Cezary; Lesyng, Bogdan; Stec, Rafał; Kieda, Claudine (Frontiers in Cell and Developmental Biology, 2025)
IntroductionDiscrepancies between preclinical tests and clinical results raise serious concerns about the appropriateness of the current methodologies. In particular, cell biology approaches neglect fundamental physical parameters despite their relevance to in vivo conditions. Oxygen availability is critical for cell reactions; thus, the lack of consideration of hypoxia as the main regulator of the tumor microenvironment (TME) leads to misinterpreted data with consequences for translational applications. In this study, we show that mitomycin C (MMC), an antineoplastic antibiotic, is rarely used in ovarian cancer (OC) treatment despite its potential efficacy; we use MMC as an example of a treatment that warrants reevaluation under microenvironmental conditions, particularly during in vitro testing.MethodsTo evaluate the effects of MMC and oxygen tension (pO2) on OC cells (SKOV3), HTA 2.0 microarrays were used, which demonstrated that hypoxia and MMC induced transcriptomic changes in OC cells. Their combination particularly emphasized the effect of pO2 modification on MMC activity. The most significant findings were verified in three other OC cell lines, namely, TOV112D, ES-2, and A2780.ResultsUnder normoxic conditions, MMC mostly affected several pathways associated with ribosome-related processes, whereas under hypoxic conditions, it induced modifications in the extracellular matrix (ECM). The most significantly upregulated gene in response to hypoxia–MMC treatment was MMP1, regulated by both MMC and hypoxia. Low pO2 levels during MMC treatment allowed the identification of important regulators, such as SPP1, and the corresponding processes, including cholesterol biosynthesis.ConclusionHypoxia modulated the effects of MMC on OC cells and identified genes that may serve as promising targets to enhance the effectiveness of MMC treatment.